Spermidine application alleviates salinity damage to antioxidant enzyme activity and gene expression in alfalfa - Lou, Yanhong (Ecotoxicology (London, England), 2018)
We investigated whether spermidine (Spd) application alleviates salinity-induced damage in alfalfa (Medicago sativa L), and explored defence mechanisms associated with stress-related ion balance, antioxidant metabolism, and gene expression. We examined the response of 30-day-old alfalfa maintained in hydroponic culture tests for 7 days and subjected to one of six treatments: half-strength Hoagland solution (control); 1% NaCl; 10 μM Spd + 1% NaCl; 20 μM Spd + 1% NaCl; 40 μM Spd + 1% NaCl; and 60 μM Spd + 1% NaCl. In salinity-stressed plants, chlorophyll b, chlorophyll a + b, and total protein showed significant decreases, while marked increases were detected in relative electrolyte leakage, H2O2 content, glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), glutathione reductase (GR) activity, the Na+/K+ ratio, and APX1, APX2, GR, and SOD gene expression levels. Chlorophyll a and total protein content markedly increased under exogenous application of 20 μM Spd, while H2O2 content, GSH, SOD, CAT, POD, GR activity, the Na+/K+ ratio, and APX2, GR, and SOD expression levels all decreased. These results indicated that exogenous application of 20 μM spermidine effectively alleviates salinity-induced damage in alfalfa. These findings could benefit alfalfa cultivation and promote the development and utilization of saline-alkali soil